An assessment of 2 watershed models to meet watershed planning needs. (2nd January 2022) - Hanson, Rebecca; Hammond Rowan, June; Green, Mark
Abstract: Hanson R, Hammond Rowan J, Green M. 2022. As assessment of 2 watershed models to meet watershed planning needs. Lake Reserv Manage. 38:16–27. Watershed models provide a quantitative approach for estimating loads, providing source load estimates, and evaluating various management alternatives to determine the best and most efficient actions to reduce pollutant loads. For watershed plans to be approved by the US Environmental Protection Agency (EPA) and state agencies and to obtain Clean Water Act Section 319 funding, a modeling component is required. In this study, we tested 2 watershed quality models, STEPL and SWAT, in a New Hampshire watershed to determine, when there are limited data available, whether the investment of resources required for a more complex model produces a more accurate understanding of phosphorus loads for the purpose of watershed planning. We found that while a simple model such as STEPL does not provide understanding of the complexities and unique nature of different watersheds, it easily provides quantitative estimates of long-term mean pollutant loads that, based on available data and state guidance, are adequate for watershed planning purposes. A more sophisticated model, such as SWAT, can provide more insight into watershed dynamics, but to be used to its full potential it requires far more data and expertise than may exist in watershed groups and municipalities involved with applied watershed management planning. We recommend that watershed plans include goals for implementing studies that produce rich datasets and more sophisticated modeling as a long-term watershed management objective to improve understanding about watershed dynamics and predict how management actions will affect pollutant loads to achieve overall water quality improvement goals.